Targeting SxIP-EB1 interaction: An integrated approach to the discovery of small molecule modulators of dynamic binding sites. Issue 1 (December 2017) - Almeida, T.; Carnell, A.; Barsukov, I.; Berry, N.
Abstract End binding protein 1 (EB1) is a key element in the complex network of protein-protein interactions at microtubule (MT) growing ends, which has a fundamental role in MT polymerisation. EB1 is an important protein target as it is involved in regulating MT dynamic behaviour, and has been associated with several disease states, such as cancer and neuronal diseases. Diverse EB1 binding partners are recognised through a conserved four amino acid motif, (serine-X-isoleucine-proline) which exists within an intrinsically disordered region. Here we report the use of a multidisciplinary computational and experimental approach for the discovery of the first small molecule scaffold which targets the EB1 recruiting domain. This approach includes virtual screening (structure- and ligand-based design) and multiparameter compound selection. Subsequent studies on the selected compounds enabled the elucidation of the NMR structures of the C-terminal domain of EB1 in the free form and complexed with a small molecule. These structures show that the binding site is not preformed in solution, and ligand binding is fundamental for the binding site formation. This work is a successful demonstration of the combination of modelling and experimental methods to enable the discovery of compounds which bind to these challenging systems.